Insights into the formation of Au@Pt dendritic core-shell nanoparticles with the aid of ultrasonication - Lee, Hu-Jun; Hanyu, Daisuke; Dao, Anh Thi Ngoc; Kaneko, Kenji (Nature Publishing Group, 2025)
Bimetallic Au@Pt dendritic core-shell nanoparticles were synthesized via co-reduction with ultrasonication, and their nanostructures were characterized to gain insights into the formation mechanism of the Pt shell on the Au core. Two types of nanoparticles, one with ultrasonication and another without, were prepared and examined by scanning transmission electron microscopy to understand the role of ultrasonication. With or without ultrasonication, a thin layer of Pt shell was present on the Au core. The ultrasonication resulted in the Pt cluster formation from precursors, the Pt cluster dispersion, the Pt granule formation, and the Pt granule collision with the Au core. Consequently, Au@Pt nanoparticles were synthesized with the Pt dendritic shell consisting of Pt granules. These findings highlight the potential of ultrasonication in the controlled synthesis of nanoparticles with unique nanostructures.